Biopsy interpretation of the gastrointestinal tract mucosa . - Montgomery, Elizabeth [ (Elizabeth A.)] , 1958-; Voltaggio, Lysandra (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
Gastrointestinal mucosal biopsies are an active part of the pathologist's day and have increased in the past few years as endoscopic screening has become more commonplace. This edition offers complete coverage of both non-neoplastic and neoplastic entities. It focuses on interpretation of neoplastic gastrointestinal mucosal biopsies